Marie d’Antioche, la mobilisation de sa parentèle dans la procédure judiciaire pour la revendication du trône de Jérusalem au xiiie siècle - Cécile Khalifa (Criminocorpus)
In the 13th century, Mary of Antioch illustrated the need for a united kinship in the face of opponents for the throne of Jerusalem. Granddaughter of Isabella Ist of Jerusalem and Aimery Ist of Lusignan, Mary of Antioch, daughter of Melisende of Lusignan and Bohemond IV of Antioch, claimed the throne of Jerusalem. Her competitor was none other than Hugh III, son of Henry of Poitiers-Antioch and Isabella of Lusignan, great grandson of Isabella Ist of Jerusalem. Faced with her competitor, Mary of Antioch claimed the title of Queen of Jerusalem. She then mobilised her Champagne relatives, descendants of Philippa of Champagne-Jerusalem, sister of her mother Melisende, to find out what their ambitions were about the throne. The aim here is to analyse the support Mary of Antioch received during her claims and how she was able to stand up to the King of Cyprus, even though the High Court of Acre rejected her appeal. Mary of Antioch had several supporters in the Holy Land, due to her kinship with several lineages such as the Briennes, and her proximity to Conradin, son of Conrad IV, son of Frederick II. The aim of this contribution will therefore be to examine the judicial strategy put in place by Mary of Antioch.